Recanalization Therapies in Acute Ischemic Stroke Patients. Issue 13 (29th September 2015) - Seiffge, David J.; Hooff, Robbert-JanVan; Nolte, Christian H.; Béjot, Yannick; Turc, Guillaume; Ikenberg, Benno; Berge, Eivind; Persike, Malte; Dequatre-Ponchelle, Nelly; Strbian, Daniel; Pfeilschifter, Waltraud; Zini, Andrea; et al.
<x xml:space="preserve">Abstract</x> Background— We explored the safety of intravenous thrombolysis (IVT) or intra-arterial treatment (IAT) in patients with ischemic stroke on non-vitamin K antagonist oral anticoagulants (NOACs, last intake <48 hours) in comparison with patients (1) taking vitamin K antagonists (VKAs) or (2) without previous anticoagulation (no-OAC). Methods and Results— This is a multicenter cohort pilot study. Primary outcome measures were (1) occurrence of intracranial hemorrhage (ICH) in 3 categories: any ICH (ICHany), symptomatic ICH according to the criteria of the European Cooperative Acute Stroke Study II (ECASS-II) (sICHECASS-II) and the National Institute of Neurological Disorders and Stroke (NINDS) thrombolysis trial (sICHNINDS); and (2) death (at 3 months). Cohorts were compared by using propensity score matching. Our NOAC cohort comprised 78 patients treated with IVT/IAT and the comparison groups of 441 VKA patients and 8938 no-OAC patients. The median time from last NOAC intake to IVT/IAT was 13 hours (interquartile range, 8–22 hours). In VKA patients, median pre-IVT/IAT international normalized ratio was 1.3 (interquartile range, 1.1–1.6). ICHany was observed in 18.4% NOAC patients versus 26.8% in VKA patients and 17.4% in no-OAC patients. sICHECASS-II and sICHNINDS occurred in 2.6%/3.9% NOAC patients, in comparison with 6.5%/9.3% of VKA patients and 5.0%/7.2% of no-OAC patients, respectively. At 3 months, 23.0% of NOAC patients in comparison with 26.9% of VKA patients and 13.9% of no-OAC patients had died. Propensity score matching revealed no statistically significant differences. Conclusions— IVT/IAT in selected patients with ischemic stroke under NOAC treatment has a safety profile similar to both IVT/IAT in patients on subtherapeutic VKA treatment or in those without previous anticoagulation. However, further prospective studies are needed, including the impact of specific coagulation tests.